2022
DOI: 10.1021/acsmaterialslett.2c00742
|View full text |Cite
|
Sign up to set email alerts
|

MOF Polymer Composites Exhibit Faster Nitric Oxide Catalysis than MOF Crystallites

Abstract: Metal–organic frameworks (MOFs), a class of crystalline solids, show promise for application as heterogeneous catalysts. Applying MOFs in industrial settings usually requires that unprocessed MOF powder be immobilized within a continuous phase, such as a polymer; however, it is unknown in general if this immobilization impacts MOF catalyst behavior. Therefore, it is necessary to directly compare unprocessed MOF powders and MOF-polymer composites as catalysts. Herein, we study the biomedically important release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…1 In general, transition metal ions with unfilled d orbitals are selected as metal centers to accept lone pairs of electrons from ligands, and ligands containing at least one polydentate functional group are selected to decoordinate metal ions. 2 Due to advantages such as simple synthesis routes, large specific surface areas, high porosities, and easy modifications, MOFs have been widely used in the fields of gas storage and separation, [3][4][5] catalysis, [6][7][8] sensing, [9][10][11] and drug delivery. [12][13][14] In these applications, the use of MOFs as fluorescent materials to construct sensors for a variety of targets is popular due to…”
Section: Introductionmentioning
confidence: 99%
“…1 In general, transition metal ions with unfilled d orbitals are selected as metal centers to accept lone pairs of electrons from ligands, and ligands containing at least one polydentate functional group are selected to decoordinate metal ions. 2 Due to advantages such as simple synthesis routes, large specific surface areas, high porosities, and easy modifications, MOFs have been widely used in the fields of gas storage and separation, [3][4][5] catalysis, [6][7][8] sensing, [9][10][11] and drug delivery. [12][13][14] In these applications, the use of MOFs as fluorescent materials to construct sensors for a variety of targets is popular due to…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Metal−organic framework (MOF) is a porous crystal material with periodic three-dimensional network structure formed by self-assembly of metal ions and organic ligands. 18,19 Due to its excellent designability, MOF has been applied inmanyfields, 20,21 including the field of TENG. 22 Khandelwal et al 23 made MOF-TENG with ZIF-8 and Kapton as active materials, the output current of 7 μA was obtained.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Specifically, the catalytic production of NO by the MOF CuBTTri is by oxidation of GSNO (S-nitrosoglutathione), which is a tripeptide that originates from within the human body. In our previous work we showed that GSNO can act as an endogenous source of NO in the presence of CuBTTri . In this NO delivery application, the NO is produced in smaller doses but over a much longer time (potentially indefinitely), which may create a permanent antimicrobial surface to prevent medical device fouling.…”
Section: Introductionmentioning
confidence: 99%
“…To pave the way for the transition of highly porous and versatile metal–organic frameworks (MOFs) from the benchtop toward real-world applications, it is important to improve their industrial processability. , One commonly applied strategy is to pelletize MOF powders, but this attenuates their properties due to the binder required and may also change their structural properties due to the applied pressure . An alternative approach is to incorporate the active material into stand-alone polymer films by producing MOF composites, also often referred to as mixed-matrix membranes (MMMs). For this approach, it is important to make sure that the porous interior of the MOF is still accessible, as this preserves its application-relevant properties (e.g., accessibility of internal porosity and open metal sites) . So far MOF-based MMMs have proven particularly useful for the separation of gases or molecules, sensing, light-harvesting applications, and biomedical applications. Studying the interface between the MOF filler and polymer is challenging and often requires significant effort and resource.…”
Section: Introductionmentioning
confidence: 99%